Discovery of Potent Dual Binding Site Acetylcholinesterase Inhibitors via Homo‐ and Heterodimerization of Coumarin‐Based Moieties. (29th June 2017) - Pisani, Leonardo; Catto, Marco; De Palma, Annalisa; Farina, Roberta; Cellamare, Saverio; Altomare, Cosimo D.
Abstract: Acetylcholinesterase (AChE) inhibitors still comprise the majority of the marketed drugs for Alzheimer's disease (AD). The structural arrangement of the enzyme, which features a narrow gorge that separates the catalytic and peripheral anionic subsites (CAS and PAS, respectively), inspired the development of bivalent ligands that are able to bind and block the catalytic activity of the CAS as well as the role of the PAS in beta amyloid (Aβ) fibrillogenesis. With the aim of discovering novel AChE dual binders with improved drug‐likeness, homo‐ and heterodimers containing 2 H ‐chromen‐2‐one building blocks were developed. By exploring diverse linkages of neutral and protonatable amino moieties through aliphatic spacers of different length, a nanomolar bivalent AChE inhibitor was identified (3‐[2‐(4‐[(dimethylamino)methyl]‐2‐oxo‐2 H ‐chromen‐7‐yloxy)ethoxy]‐6, 7‐dimethoxy‐2 H ‐chromen‐2‐one (6 d ), IC50 =59 nm ) from originally weakly active fragments. To assess the potential against AD, the disease‐related biological properties of6 d were investigated. It performed mixed‐type AChE enzyme kinetics (inhibition constant K i =68 nm ) and inhibited Aβ self‐aggregation. Moreover, it displayed an outstanding ability to protect SH‐SY5Y cells from Aβ1‐42 damage. Abstract : Power in pairing : Acetylcholinesterase inhibition can be strongly improved by connecting weakly active smaller fragments through a suitable spacer. A dimerization strategy is described that leads to a coumarin‐based inhibitor endowed with nanomolar affinity. The inhibitor can bind both catalytic and peripheral anionic subsites, decrease amyloid aggregation, and protect SH‐SY5Y cells from Aβ1–42 insults.